A Review of Official Documents and Literature on the Forgotten Victims of Parental Incarceration in South Africa - Magadla-Mateyise, Afika Fikiswa; Zenzile, Enoch (Research in Social Sciences and Technology- OpenED Network, 2024)
This article is a literature synthesis of the living conditions of black children after their parent's imprisonment. In Africa, the prison population currently stands at 1,194,497, while in South Africa, 147,922 people were being held in correctional facilities as of January 2021. Parental incarceration has affected all children, regardless of race, age, or cultural background. An increasing amount of research indicates that children with incarcerated parents are prone to internalized behaviors such as depression, anxiety, and withdrawal, as well as externalized behaviors including criminality and substance use. They may also experience cognitive delays, academic struggles, and insecure attachments in their relationships with both their imprisoned parents and primary caregivers. The term